How would I solve this:
((x^(3)-x^(2)-4x+8))/(x-1)
3 answers
would the answer be ((x^(2)-4))(x+2)
x-1 does not divide into your numerator, so
there is no simplification.
if you want to solve the equation
((x^(3)-x^(2)-4x+8))/(x-1) = 0 then
http://www.1728.com/cubic.htm?a=1&b=-1&c=-4&d=8
there is no simplification.
if you want to solve the equation
((x^(3)-x^(2)-4x+8))/(x-1) = 0 then
http://www.1728.com/cubic.htm?a=1&b=-1&c=-4&d=8
Tiana, please do not attach a new problem to end of a series of replies.
Click on "post a new problem" at the top to start your problem
Your question really puzzles me.
I hope your text does not introduce algebra or variables in this way.
There is no need for any variables or equation for this problem.
Each of the three fisherman got 8 fish,
so there were 3x8 or 24 fish.
End of problem!
Click on "post a new problem" at the top to start your problem
Your question really puzzles me.
I hope your text does not introduce algebra or variables in this way.
There is no need for any variables or equation for this problem.
Each of the three fisherman got 8 fish,
so there were 3x8 or 24 fish.
End of problem!